Towards efficient consumer protection - Huarag Guerrero, Enrico Marcel (2021)
Currently, in economic terms, we face a reality in which resources are scarce and needs are unlimited. Therefore, the most efficient way to manage these scarce resources is to determine a certain value that the market appreciates it. That value, the market is often assigned the price. Indeed, high prices in the market indicate that there is much demand for a product or service, and create incentives for the entry of new suppliers. This situation naturally occurs when markets operate with reasonable efficiency, however there are certain circumstances in which markets do not get efficient results because the prices of goods or services offered to consumers are not consistent with each other. In this circumstance state intervention supported by regulatory standards and designed to correct the imbalances that inevitably will occur public bodies.